Ni (II), Cd (II) And Cr (IV) Contamination In Groundwater At Pulau Burung Decommissioned Landfill Site And Metal Biosorption Using Trichoderna Sp - Chew , Ann Won (2011)
Historical accumulation of heavy metals in landfills has caused an increased leaching in groundwater all around the world. The elevated concentration of heavy metals in groundwater can cause environmental problems in most of the surrounding areas. The main objectives of this study are to determine the concentration of metal ions (Ni, Cr and Cd) in the groundwater of Pulau Burung landfill located within Byram Forest Reserve at 5º 24'N, 100º 24'E in Penang, Malaysia, to study the biosorption of Trichoderma sp. on nickel, cadmium and chromium in the contaminated groundwater.